2002
DOI: 10.2337/diacare.25.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Blood Glucose Testing at Alternate Sites

Abstract: ALTHEA ANAGNOSTOPOULOS, MS 2OBJECTIVE -To measure hematocrit (Hct) and glucose concentration in capillary blood drawn from the fingertip and forearm of a group of 50 nonfasting subjects with diabetes. RESEARCH DESIGN AND METHODS -Hct was determined indirectly by measuringHb with the HemoCue B-Hemoglobin Photometer. Glucose was assayed with the HemoCue B-Glucose Analyzer, chosen as the independent control assay, and the Sof-Tact Blood Glucose System. Testing session with each subject lasted ϳ30 min and consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The difference between the whole-blood glucose levels obtained by capillary blood sampling from the forearm and from the finger was reported to be statistically insignificant, but that assessment was performed in a limited number of subjects [16]. However, clinical practice usually requires additional validation in a sufficiently large subject population as well as over a wide range of glucose concentrations, and these requirements served as the motivations for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the whole-blood glucose levels obtained by capillary blood sampling from the forearm and from the finger was reported to be statistically insignificant, but that assessment was performed in a limited number of subjects [16]. However, clinical practice usually requires additional validation in a sufficiently large subject population as well as over a wide range of glucose concentrations, and these requirements served as the motivations for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intraclass correlation coefficient values were statistically highly significant (P<0.0001), thereby indicating that GA correlated well with both GF and GV. Similar values between these 2 different types of correlation coefficient not only imply insignificant difference in the measurement characteristics between the groups but also reflect that no significant error was introduced in our experiment, thereby satisfying the pre-requisite of the simple linear regression analysis usually performed in glucose measurement [14,16] as per the FDA recommendations for approval [19].…”
Section: ) Intraclass Correlation Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for blood glucose, no significant difference was observed between the fingertip and venous blood assays in this study, which is consistent with a previous report. 2 In the blood cell count measurement, we reviewed the procedures and were able to successfully prevent coagulation of the specimens by thoroughly mixing the contents by snap-shaking after the fingertip blood collection. Yang, et al 1 reported a difference in the WBC count between fingertip blood and venous blood, and also that by repeated collection there was a decrease in the WBC count in fingertip blood.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] For example, correlations between assay results using blood samples collected from a vein, such as the ante-cubital vein (hereinafter referred to as "venous blood"), and fingertip blood samples have been reported for biochemical tests. 4 In addition, it has been suggested that hematological tests can be also measured in fingertip blood samples as long as test values are within the reference intervals established by the Japanese Committee for Clinical Laboratory Standards and if the following two conditions are met: capillary-collected blood is promptly transferred into a microliter-scale blood collection tube containing ethylenediaminetetraacetic acid (EDTA) and contamination with interstitial fluid by forced blood extrusion is avoided.…”
mentioning
confidence: 99%